Traditional Methods of Diabetes Mellitus Treatment - Khalid Abdulkareem Mohammed (World Journal of Experimental Biosciences, 2023)
Diabetes mellitus is one of the most common metabolic diseases in the world, and the incidence of this disease is not limited to specific age groups, and it appears among men and women and there is no effect on gender, age, and geographic area on the outbreak of this disease. Synthetic and natural materials have been used to control blood sugar levels in diabetics. The current study sheds light on the importance of this disease and the extent of its spread in the world, in addition to its most important types, which are Insulin-dependent diabetes mellitus (IDDM) Insulin-independent diabetes mellitus (IIDM), and Gestational diabetes. The current study showed the most important herbal extracts that were used and are still used today in many countries to control hyperglycemia in diabetics, especially Brassica olerace. The effect of these herbal extracts is due to the presence of some active substances that reduce high blood sugar levels, and the most important of these substances are phenols and alkaloids. The effect of these substances on insulin-producing cells was discussed, as well as their direct and indirect effect on controlling high blood sugar in laboratory animals and people suffering from various types of diabetes. The study concluded that the use of herbal medicine is effective in reducing hyperglycemia in patients with diabetes, in addition to being safe and having no side effects on patients who use them.
Keywords: Diabetes mellitus, Herbal medicine, Insulin-dependent diabetes, Insulin-independent diabetes.